Decarbonisation of the electricity sector – is there still a place for markets? - Keay, M; Rhys, J; Robinson, D (Oxford Institute for Energy Studies, 2012)
Governments across the OECD are committed to ambitious reductions in CO2 emissions. Electricity is central to this agenda as the sector where the earliest and steepest cuts will be sought. A number of countries, like the UK, are already in the process of reforming their electricity markets in order to ensure the delivery of the huge quantities of low carbon investment which will be needed; these reforms have involved a more central role for the government in decision-making, and in underwriting investments. The paper considers whether the role of market forces is inevitably going to be increasingly limited by the existence of rigorous environmental targets, and examines a number of options which could still leave a significant degree of competition. It also looks at the wider changes which will accompany decarbonisation of the sector, for instance the increasing importance of the demand-side and the need for further changes in wholesale market structures. It concludes that governments need to address the wide range of issues involved in a coherent manner and at an early stage if the process of decarbonisation is to be undertaken successfully.